The Relationship Between Physical Activity And Peak Height Velocity In Children Aged 9 – 11 Years (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2022)
The purpose of this research was to determine the relationship between physical activity and the age of PHV in children aged 9-11 years. The method used in this research is a test survey with data collection techniques using questionnaires and measurement tests. The population in this research is SSB Tugumuda athletes and grade 4 students at SDN Karangjati 04. The samples were taken from as many as 29 boys from SSB Tugumuda and 23 boys from SDN Karangjati 04 aged 9-11 years. The sampling technique uses purposive sampling. The data analysis technique in this research used the Pearson bivariate correlation test. The results showed that 1) The level of physical activity of 1 child (1.9%) had a